REDESIGN VISUAL IDENTTY PRODUK KOPI “YOU COFFEE” WONOSALAM GUNA MENINGKATKAN BRAND AWARENESS - Nurdiansyah, Pungky Gilang; Yurisma, Dhika Yuan; Riqqoh, Abdullah Khoir (Jurnal Art Nouveau, 2018)
In this research, researchers conducted observations directly and found that coffee products from “You Coffee” Wonosalam does not have a logo as visual identity that can describe the characteristics of the products. In this redesign, the researcher will focus on the new logo as visual identity design process in redesign visual identity effort.The concept of the redesign that has been designed is prosperity that obtained from the analysis of data and keywords. The concept is to make an impression to the public and consumen that products of “You Coffee” is the prosperity of exelsa Wonosalam coffee by making a visual identity that can describe the characteristics of “You Coffee”.In addition to creating a better logo, this design also makes the brand guideline that aims to provide an explanation of the values and essence of the “You Coffee” brand along with guidelines for the use of their logos and application for design execution. Implementation of design on stationary sets, brochure, x-banner, packaging, posters and merchandise is intended as an informative media that can help the target audiences in knowing about “You Coffee” Wonosalam.